Market Orientation, Entrepreneurial Orientation, and Competitive Advantage of Tourism Villages in Batu City: An Importance-Performance Analysis - Adya Hermawati; Armanu Thoyib; Aviv Yuniar Rahman; Triana Dewi Salma; Dwi Farotul Khasanah; Rizki Dwi Ariyanto (Bulletin of Community Engagement, 2026)
Tourism villages have become a strategic instrument for regional economic development in Indonesia, yet systematic evaluations of their managerial performance remain limited. This study examines the perceived importance and performance of Market Orientation, Entrepreneurial Orientation, and Competitive Advantage in tourism villages across Batu City, East Java, using Importance-Performance Analysis (IPA). Primary data were collected through a structured questionnaire distributed to 1,152 respondents representing 384 Neighbourhood Units (RTs) across 24 villages in three sub-districts of Batu City. Indicators for each variable were assessed on a five-point Likert scale, and importance weights were derived via Principal Component Analysis. Results indicate that all three variables were rated at a good performance level (mean scores 3.90–4.00), with importance weights ranging from 0.53 to 0.75. For Market Orientation, indicators related to understanding tourist needs, market comprehension, destination competitiveness, and service quality maintenance were positioned in Quadrant II (Keep Up the Good Work), signaling sustained strategic strengths. For Entrepreneurial Orientation, long-term vision, business independence, youth engagement, and learning from experience emerged as high-importance, high-performance priorities. For Competitive Advantage, professional tourism management, destination uniqueness, cultural heritage, and continuous innovation were identified as core competitive strengths. No indicators fell in Quadrant I (Concentrate Here), suggesting the absence of critical performance gaps. These findings provide actionable strategic guidance for tourism village managers and policymakers in sustaining and enhancing the competitive position of Batu City as a leading tourism destination in East Java.